Earlier Apgar score increase in severely depressed term infants cared for in Swedish level III units with 40% oxygen versus 100% oxygen resuscitation strategies: a population-based register study. - Hellström-Westas, Lena; Forsblad, Kristina; Sjors, Gunnar; Saugstad, Ola Didrik; Björklund, Lars; Marsal, Karel; Källén, Karin (Pediatrics, 2006)
OBJECTIVES. The aim of this study was to evaluate whether a resuscitation strategy based on administration of 40% oxygen influences mortality rates and rates of improvement in 5-minute Apgar scores, compared with a strategy based on 100% oxygen administration. METHODS. A population-based study evaluated data from 4 Swedish perinatal level III centers during the period of 1998 to 2003. During this period, the centers used either of 2 resuscitation strategies (initial oxygen administration of 40% or 100%). Live-born, singleton, term infants with 1-minute Apgar scores of < 4, with a birth weight appropriate for gestational age, and without major malformations were included in the study (n = 1223). RESULTS. Infants born in hospitals using a 40% oxygen strategy had a more rapid Apgar score increase than did infants born in hospitals using a 100% oxygen strategy; however, no difference remained at 10 minutes. The mean Apgar score increased from 2.01 at 1 minute to 6.74 at 5 minutes in the 2 hospitals initiating resuscitation with 40% oxygen, compared with 2.01 to 6.38 in the 2 hospitals using 100% oxygen, with a mean difference in Apgar score increases of 0.36. At 5 minutes, 44.3% of infants born in the hospitals using 100% oxygen had an Apgar score of < 7, compared with 34.0% of infants at the hospitals using 40% oxygen. At 10 minutes, the mean Apgar scores were 8.16 at the hospitals using 40% oxygen and 8.07 at the hospitals using 100% oxygen. There were no significant differences in rates of neonatal death, hypoxic ischemic encephalopathy, or seizures in relation to the 2 oxygen strategies. CONCLUSION. Severely depressed term infants born in hospitals initiating resuscitation with 40% oxygen had earlier Apgar score recovery than did infants born in hospitals using a 100% oxygen strategy.
Keywords: Resuscitation: methods; Registries; Newborn; Infant; Humans; Apgar Score; Oxygen: administration & dosage; Diseases: therapy; Severity of Illness Index; Sweden; Time Factors